Steamed open - Ross, Barbara, 1953- (Ross, Barbara, 1953- Maine clambake mystery., 2018)
It's summertime in Busman's Harbor, Maine, and the clamming is easy--or it was until a mysterious new neighbor blocks access to the beach, cutting off the Snowden Family Clambake's supply. Julia Snowden is just one of many townspeople angered by Bartholomew Frick's decision. But which one of them was angry enough to kill? Beachcombers, lighthouse buffs, and clammers are outraged after Frick puts up a gate in front of his newly inherited mansion. When Julia urges him to reconsider, she's the last to see him alive--except the person who stabs him in the neck with a clam rake. As she pores through a long list of suspects, Julia meets disgruntled employees, rival heirs, and a pair of tourists determined to visit every lighthouse in America. They all have secrets, and Julia will have to work fast to expose the guilty party--or see this season's clam harvest dry up for good.